Peran Aparat Penegak Hukum dalam Perlindungan Korban KDRT: Persepktif Viktimologi - Imelda Sihombing; Regita Angraini Lubis (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This study examines the role of law enforcement officers in providing protection for victims of domestic violence (DV) in Indonesia from a victimological perspective. The research focuses on how the police, prosecutors, and courts implement comprehensive legal protection, encompassing physical, psychological, and social aspects of the victims. The study employs a qualitative descriptive method with a normative-juridical and sociological approach, combining literature review and case analysis. The findings indicate that law enforcement officers play a strategic role; however, the effectiveness of victim protection remains limited due to constraints in professional capacity, lack of operational guidelines, formalistic orientations, and social stigma against victims. This study emphasizes the importance of integrating human rights (HR) and victimology principles in law enforcement practices, including officer training, strengthening standard operating procedures, legal and psychological assistance, and periodic evaluation of policy implementation. The application of these strategies is expected to enhance victim protection, reduce the risk of revictimization, and strengthen substantive justice. This research contributes to the development of more humanistic, responsive, and socially relevant policies for DV victim protection.